Investigation of the aerotropolis concept and its transferability around the world. (January 2023) - Corrêa Pereira, Anna Carolina; Milne, David; Timms, Paul
Abstract: Academic and industrial literature highlight the importance of airport-driven development (ADD) for the 21st Century. Several different types of ADD concepts have been defined, such as aerotropolis and airport city, but there are often substantial differences between authors about definitions. Such differences can potentially create confusion when ADD concepts are used by airport planners in their planning documents (e.g., master plans) and the marketing materials (e.g., brochures and airport websites). Given that large amounts of investment can often depend upon the marketing of a particular ADD concept, such confusion is highly problematic for the air transport industry. However, previous research has not explicitly addressed this issue. To help fill this research gap, the current paper has four different purposes, to: (1) compare definitions of the airport-driven development concepts in the academic literature, (2) compare definitions with real-life examples given by researchers; (3) compare academic definitions and examples with industry usage, as found on airport websites and in airport planning documents; and (4) investigate aspects of the transferability of the ADD concepts (from one region to another and from the academic literature to the industry and vice-versa). Using information from airport websites and master plans, it was found that the terms aerotropolis and airport city are used interchangeably by researchers but not by the industry. However, the use of terms by the industry depends heavily upon the (continental) location of airports, with the analysis presented in the paper distinguishing between airports in North America, Latin America, South and East Asia, Europe and the Middle East. Such analysis enables conclusions to be made about the transferability of ADD concepts, originating in the Global North, to the Global South. Highlights: Airports examples of airport-driven development concepts differ by researchers. . Airports examples of airport-driven development concepts in the academic literature diverge from the industry. The way the industry classifies airports to airport-driven development concepts depends on the location of airports. Proximity and strategic investments influence the transferability of the concepts.